2018
DOI: 10.1007/s12020-018-1572-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal soybean diet during lactation alters breast milk composition and programs the lipid profile in adult male rat offspring

Abstract: Maternal intake of soybeans in lactation changes the lipid content of breast milk and programmed offspring for phenotype of the lower metabolic risk, with lower serum TC and LDL, and seems to protect the progeny of alterations in glucose metabolism despite the higher lipid content. The difference in fat content of breast milk and the higher isoflavones content of soy diet are possible imprinting factors that could program the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
4
9
0
Order By: Relevance
“…Perinatal environment, including lactation, is also a very important programming window considered to play a critical role in the development of the offspring [1]. Though the breast milk is mainly affected by the lactation diet, it is inevitable that gestational diet would also have certain influence on the composition [40]. Therefore, it is important to study the composition of nutrients and hormones in breast milk, which was what we neglected when designing the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal environment, including lactation, is also a very important programming window considered to play a critical role in the development of the offspring [1]. Though the breast milk is mainly affected by the lactation diet, it is inevitable that gestational diet would also have certain influence on the composition [40]. Therefore, it is important to study the composition of nutrients and hormones in breast milk, which was what we neglected when designing the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing its etiology is essential to face the global epidemic. This creates a challenge since the pathway to obesity in many individuals begins before birth; a predisposition to obesity can occur through epigenetic and other forms of early programming, and obesity and its metabolic consequences result from physiological changes set during fetal and early postnatal development [17][18][19].…”
Section: The Early-life Origins Of Obesitymentioning
confidence: 99%
“…In a study developed by our research group, we identified that the maternal intake of soybeans in lactation changed the lipid content of breast milk and programmed offspring for a phenotype of the lower metabolic risk. The difference in fat content of breast milk and the higher isoflavones content of soy diet are possible imprinting factors that could program the offspring [18]. This is particularly important because it highlights the dual role of nutritional alterations, whether as reprogramming strategies to prevent disease or leading to adult disease [40].…”
Section: Metabolic Pathways and Epigeneticsmentioning
confidence: 99%
“…Commercial organic soy and soy protein isolates were processed to inactivate antinutritional factors. After, they were transformed into flour for the preparation of the soybean experimental diet, according to the methods of Soares et al 26 and Vieira et al 22 . The centesimal composition of the soy flour was analyzed according to reference methods 27 .…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Recently, our group observed changes in the lipid profile of breast milk from lactating rats placed on a soybean diet, which programmed adult offspring for a phenotype of lower metabolic risk, low total cholesterol (TC) and LDL-cholesterol, and protection against changes in glycemic metabolism 22 . However, soy protein isolate consumption in the same model programmed the offspring to negative effects on body composition, lipid profile, and glycemic homeostasis, generating a profile of higher metabolic risk in adulthood 23 .…”
Section: Introductionmentioning
confidence: 99%